2016
DOI: 10.1007/s40948-016-0034-2
|View full text |Cite
|
Sign up to set email alerts
|

Geopolymer as well cement and its mechanical integrity under deep down-hole stress conditions: application for carbon capture and storage wells

Abstract: With regard to the safety, environmental impact and sustainability of carbon capture and storage (CCS) projects, the integrity of injection and production wells plays a major role. In a CCS project, mechanical integrity of well cement should be maintained to sustain the required mechanical strength throughout the life of an oil/gas and CO 2 sequestration well. One of the major issues with existing Portland cement based oil well cement is cement degradation in CO 2 -rich environment. On the other hand, geopolym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…Geopolymers, in the family of inorganic aluminosilicate binder, has received extensive interests because of high temperature resistance [70,[102][103][104][105], low permeability [106][107][108][109][110], strong bonding and good durability [51,[111][112][113], excellent chemical corrosion resistance [114][115][116][117][118], and environmental friendliness [119,120], etc. Some of the uses that have been investigated for alkaline activated materials are: as sustainable construction material [121][122][123][124][125][126], mine backfilling [127,128], porous spheres as novel pH buffers [129,130], bricks [71,112,131,132], porous thermal insulation material [133], as road material [134], for immobilization of toxic metals and nuclear waste management [135][136][137][138][139][140], coatings for concrete [141]…”
Section: Curing Temperature and Timementioning
confidence: 99%
“…Geopolymers, in the family of inorganic aluminosilicate binder, has received extensive interests because of high temperature resistance [70,[102][103][104][105], low permeability [106][107][108][109][110], strong bonding and good durability [51,[111][112][113], excellent chemical corrosion resistance [114][115][116][117][118], and environmental friendliness [119,120], etc. Some of the uses that have been investigated for alkaline activated materials are: as sustainable construction material [121][122][123][124][125][126], mine backfilling [127,128], porous spheres as novel pH buffers [129,130], bricks [71,112,131,132], porous thermal insulation material [133], as road material [134], for immobilization of toxic metals and nuclear waste management [135][136][137][138][139][140], coatings for concrete [141]…”
Section: Curing Temperature and Timementioning
confidence: 99%
“…The potential for using geopolymers for well cementing has been recently explored by Nasvi and co-workers [54][55][56][57][58] in laboratory-based studies. Other researchers are now exploring the use of this system, particularly where CO 2 sequestration is being considered, as the system is not readily carbonated [59].…”
Section: Alkali Activated or Geopolymeric Systemsmentioning
confidence: 99%
“…All over the world, anthropogenic emissions of greenhouse gases have been a major concern with carbon dioxide (CO 2 ) playing a major role in these greenhouse gas emissions [1]. Hence, it is essential to reduce carbon dioxide emissions if global warming is to be effectively reduced.…”
Section: Introductionmentioning
confidence: 99%
“…In a CO2 rich environment, Portland cement will be unstable and will have reduced strength, cement degradation, and increased permeability and will be subjected to chemical attacks [7]. On the other hand, researchers [1,3,8] have found that geopolymer possesses excellent acid resistant characteristics, high strength and low shrinkage compared to OPC. Geoploymer is an aluminasilicate cementitious material, which can be synthesized by mixing the source material (fly ash, metakaolin, slag etc.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation